Simple fabrication of 12 μm thin nanocomposite fuel cell membranes by direct electrospinning and printing - Breitwieser, Matthias; Klose, Carolin; Klingele, Matthias; Hartmann, Armin; Erben, Johannes; Cho, Hyeongrae; Kerres, Jochen; Zengerle, Roland; Thiele, Simon (Journal of Power Sources, 2017)
Direct membrane deposition (DMD) was recently introduced as a novel polymer electrolyte membrane fabrication method. Here, this approach is extended to fabricate 12 μm thin nanocomposite fuel cell membranes. Poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) nanofibers are directly electrospun onto gas diffusion electrodes. By inkjet-printing Nafion ionomer dispersion into the pore space of PVDF-HFP nanofiber mats, composite membranes of 12 μm thickness were fabricated. At 120 °C and 35% relative humidity, stoichiometric 1.5/2.5 H2/air flow and atmospheric pressure, the power density of the DMD fuel cell (0.19 W cm-2), was about 1.7 times higher than that of the reference fuel cell (0.11 W cm-2) with Nafion HP membrane and identical catalyst. A lower ionic resistance and, especially at 120 °C, a reduced charge transfer resistance is found compared to the Nafion HP membrane. A 100 h accelerated stress test revealed a voltage decay of below 0.8 mV h-1, which is in the range of literature values for significantly thicker reinforced membranes. Finally, this novel fabrication approach enables new degrees of freedom in the design of complex composite membranes. The presented combination of scalable deposition techniques has the potential to simplify and thus reduce cost of composite membrane fabrication at a larger scale.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Composite membrane; Direct membrane deposition; Electrospinning; Inkjet-printing; PEMFC